Anticipated Difficult Airway During Obstetric General Anesthesia: Narrative Literature Review and Management Recommendations. Issue 2 (24th June 2021) - Mushambi, M.C.; Athanassoglou, V.; Kinsella, S.M.
Abstract : ( Anaesthesia . 2020;75:945–961) The Obstetric Anaesthetists' Association (OAA) and the Difficult Airway Society (DAS) issued guidelines for difficult tracheal intubation in pregnant women in 2015. Many other organizations have published guidelines for difficult intubation in non-obstetric patients. This report aimed to review literature on difficult intubation in pregnant women and specifically address antenatal multidisciplinary planning for patients with anticipated and/or known difficult airway including awake tracheal intubation.